2016
DOI: 10.1158/1078-0432.ccr-15-1739
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of c-Myb Pathway by Aberrant Expression of Proto-oncogene MYB Provides the Basis for Malignancy in Adult T-cell Leukemia/lymphoma Cells

Abstract: Our data demonstrate that c-Myb pathway overactivation caused by unbalanced c-Myb-9A overexpression is associated with disorders in cellular homeostasis and consequently, accelerated transformation, cell proliferation, and malignancy in ATL cells. These data support the notion of the c-Myb pathway as a promising new therapeutic target for ATL. Clin Cancer Res; 22(23); 5915-28. ©2016 AACR.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 52 publications
(57 reference statements)
0
31
0
Order By: Relevance
“…The well-known transcription factor c-Myb has been studied extensively in solid tumors and blood cell malignancies due to its roles in cell proliferation, differentiation, and survival [47] . However, c-Myb is also intimately associated with cellular metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The well-known transcription factor c-Myb has been studied extensively in solid tumors and blood cell malignancies due to its roles in cell proliferation, differentiation, and survival [47] . However, c-Myb is also intimately associated with cellular metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Along these lines, we failed to detect c-Myb expression in control MF, whereas in TAMs c-Myb was detected at the RNA level and in nuclear extracts at the protein level. c-Myb contributes to the development of leukemia (50) and several solid tumors, and previous works predominantly focused on c-Myb in cancer cells (51,52). The role of c-Myb within cells of the TME has not yet been adequately addressed.…”
Section: Discussionmentioning
confidence: 99%
“…The aberrant expression of MYB was also identified in colon carcinoma, 29 pancreatic cancer, 11 and acute leukemia. 13,14 Furthermore, the overexpression of MYB is correlated with poor prognosis of colorectal cancer. 30 On the contrary, some studies also indicated that MYB might have tumorsuppressor role in cancer.…”
Section: Discussionmentioning
confidence: 99%